Data: Assessing consistency in the aerobic co-composting of faecal sludge and food waste in a municipality in Ghana - Gbenatey Nartey, Eric; Sakrabani, Ruben (Cranfield University, 2023)
Data on feedstock and co-composting process. DFS means dewatered faecal sludge while FW means food waste.
Keywords: Batch'; 'composting pile'; 'nitrogen'; 'E.coli'; 'compost'; 'pH'; 'feedstock'